Leiomyosarcoma of the Skull Base—A Diagnostic Challenge - May, John S. (1992)
Soft tissue sarcomas often present a frustrating diagnostic challenge for the pathologist as well as the surgeon. Despite the development of better defined criteria for histopathologic and immunohistochemical evaluation, definitive diagnosis may not be immediately apparent. We report two cases of leiomyosarcoma of the skull base that presented with the clinical diagnosis of schwannoma, a diagnosis confirmed on initial histopathologic examination. It was only after closer review and special immunohistochemical studies that the diagnosis of leiomyosarcoma was made. The methods for diagnosing such tumors using both standard histopathologic criteria and immunohistochemical methods are reviewed. We suggest that all extracranial soft tissue tumors of the skull base be examined by both techniques to avoid delayed or missed diagnosis.